A consensus on the utility of the anti-müllerian hormone assay in the assessment of ovarian reserve and gynecological conditions among Indian gynecologists - Pai, Rishma D.; Pai, Hrishikesh D.; Palshetkar, Nandita; Singh, Rakhi; Soni, Anju; Kale, Ashish; Kumar, Priti; Vyas, Lila; Saxena, Mitra; Tayade, Surekha; Pranesh, Gautham; Sengupta , Sohini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Infertility is a global issue that causes distress. Serum anti-Müllerian hormone (AMH) and antral follicle count are reliable ovarian reserve markers. The stability of serum AMH levels throughout the menstrual cycle makes monitoring ovarian function decline convenient. This consensus aimed to develop recommendations for the application of the AMH assay in assessing ovarian reserve and broader clinical decision-making among gynecologists in India. A modified Delphi method was used, with a panel of 10 expert gynecologists and 2 lab experts from India, to establish an expert consensus. A questionnaire consisting of 29 consensus statements was administered, covering topics related to ovarian reserve, AMH markers, assay reliability, performance, and specific conditions such as ovarian tumors and endometriosis. Through two rounds of the modified Delphi method, 21 consensus statements were ultimately formulated. The consensus was determined using an 80% cutoff. The panel reached a consensus on 19 statements and a moderate consensus on two, emphasizing the significance of AMH testing in evaluating ovarian reserve and reproductive aging. The panel agreed that AMH assays were valuable in predicting ovarian response to fertility treatments, diagnosing polycystic ovary syndrome and endometriosis, and guiding fertility preservation. It was concluded that AMH testing is crucial for infertility management in India, offering insights into ovarian reserve and reproductive aging. Standardized automated assays ensure speed and precision, aiding in diagnosing fertility conditions, predicting treatment responses, and preserving fertility during therapy. International standards for accurate interpretation are imperative. Overall, AMH testing plays a pivotal role in personalized fertility care in India.